Estimation of the Speed of the Vehicle Using MATLAB - Bala, Rajni; Marwaha, Anupma; Gupta, Megha; Sharma, Udit; Kishore, Gaurav; Rishika; Goel, Himanshu; Bansal, Gaurav; Marwaha, Sanjay (Asian Journal of Electrical Sciences, 2022)
The research paper uses image processing to exhibit moving car video sequences and estimates their speeds. In this paper, grayscale is utilized by the MatLAB program to pre-process video images and give a stream of legitimate video footage of traffic. This article’s challenge uses a deep studying method that wishes a vast quantity of computation for training. Thus, Authors determined to lessen the scope of the challenge to teach a version that could examine one-of-a-kind site visitors’ velocity symptoms and symptoms.